The association between personality traits and stress with nightmare frequency: an online study - Gessert, Johanna; Schredl, Michael (Dreaming, 2023)
Several studies explored the association between nightmare frequency and trait (neuroticism and openness) and state (current stress level) factors. The current online study investigated these associations using a nonrepresentative sample (N = 276). It was expected that both state and trait variables impact the nightmare frequency and the hypothesis that state factors might mediate the association between trait factors and the nightmare frequency. Results showed that both state and trait factors are independently associated with nightmare frequency. In contrast to Schredl (2003), we did not find a mediating effect of state factors on the association between nightmare frequency and trait factors. The findings support the neurocognitive model of nightmare etiology (Levin & Nielsen, 2007). (PsycInfo Database Record (c) 2023 APA, all rights reserved)